REKTOR-rektor UGM : bibliografi pendidikan Ana Nadya Abrar... [et al.] ; editor, Ana Nadhya Abrar, B.R. Suryo Baskoro - Abrar, Ana Nadhya; Baskoro, B.R. Suryo (Gadjah Mada University Press, 2004)
xxviii, 327 hlm. ilus. 25 cm.